2014
DOI: 10.1080/10408398.2011.627519
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Protein's and Dietary Acid Load's Influence on Bone Health

Abstract: A variety of genetic, mechano-response-related, endocrine-metabolic, and nutritional determinants impact bone health. Among the nutritional influences, protein intake and dietary acid load are two of the factors most controversially discussed. Although in the past high protein intake was often assumed to exert a primarily detrimental impact on bone mass and skeletal health, the majority of recent studies indicates the opposite and suggests a bone-anabolic influence. Studies examining the influence of alkalizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 76 publications
2
34
1
1
Order By: Relevance
“…While future research groups may suggest averaging multiple spot‐tests throughout the day to index NAE, it is advised that urine is a complex buffered solution that precludes averaging . In summary, 24‐hour collections are required for NAE measurement …”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…While future research groups may suggest averaging multiple spot‐tests throughout the day to index NAE, it is advised that urine is a complex buffered solution that precludes averaging . In summary, 24‐hour collections are required for NAE measurement …”
Section: Discussioncontrasting
confidence: 81%
“…Our data also captured the known fluctuation in urine pH over a day where 64% of participants had maximum and minimum pH >1.5 units apart. In light of these findings, we agree with Remer et al . that spot‐tested urine pH does not predict the dietary acid load.…”
Section: Discussionmentioning
confidence: 99%
“…One of the noncontrolled Paleolithic diet-intervention studies also showed a decrease from baseline in calcium excretion after 10 d consumption of the Paleolithic diet (22). The low-salt, high-protein, and alkalizing properties of Paleo nutrition may substantially contribute to a healthy calcium balance (42)(43)(44).…”
Section: Safety Concernsmentioning
confidence: 99%
“…Although in the past high protein intake was often assumed to exert a primarily detrimental impact on bone mass and skeletal health, the majority of studies indicate the opposite. A low-protein diet is associated with a higher risk of hip fractures, however, only under conditions of adequate Ca intake (83,84) .…”
Section: Discussionmentioning
confidence: 99%